DIVERSIFIKASI PRODUK OLAHAN BERBAHAN DASAR IKAN LELE DAN IKAN NILA DI KELURAHAN HOLLO KECAMATAN AMAHAI KABUPATEN MALUKU TENGAH - Louretha Thenu, Johanna; A. B. Nikijuluw, Fiona; Retno Aris, Wahyu; Robinson Wenno, Max (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2022)
The community service activity was mainly purposed to increase the knowledge and skills of the community in processing various fishery products made from catfish and tilapia in Hollo Village, Amahai District, Central Maluku Regency. The targets of this activity were people that cultivate catfish and tilapia and process post-harvest product in Hollo Village. The methods used are counseling, training/practice and evaluation. Based on the observation and evaluation process, it showed that people’s knowledge and skills were increasing in terms of processed fish diversification using catfish and tilapia. The community has obtained new knowledge about different fish-based processing product. Moreover, that knowledge was applied, and their skills were improved. The activity provides chance for the community to raise up their income by selling the new product. Additionally, the participants have been motivated to process and market their products. Their response was very enthusiastic in following the whole process.